What makes internal medicine attractive for the millennial generation? A survey of residents in internal medicine in Switzerland (Swiss Medical Weekly, 2019)
AIMS A new generation of physicians, millennials (also known as Generation Y), are entering residency programmes in internal medicine, and these young men and women learn and work in ways that are different from those of past generations. The aim of the present study was to investigate aspects contributing to the attractiveness to young residents of a career in general internal medicine (GIM) compared with medical subspecialties (SUB). METHODS In a cross-sectional online survey, we included residents working in residency facilities in GIM in German-speaking Switzerland. A total of 1818 junior residents were eligible. We looked for personal preferences, characteristics, and criteria influencing the choice of a career in GIM or SUB. RESULTS 392 out of 1818 (22%) residents participated in the survey (66% females); they had been in clinical training for 35.5 months on average. 87% of the respondents aspired to a title in GIM, and 29% of these to a SUB title as well. 71% of the women chose GIM and not a SUB vs 58% of the men (p